Bellezza, terrore ed esistenza - Donà, Massimo (Scenari, 2021)
Art is a terrible and exciting experience; art, considered for centuries the cradle of beauty, is destined to have nothing to do with the wonderful objects that are dear to its past. By now we are discovering that, perhaps, art has never really had anything to do with beauty intended as the quality of certain objects (the so-called works of art), but always and only with their bare existence; existence that is never reduced to the purposes that characterize the horizon, human, too human, of signification; existence that continues, tireless, to reflect the original senselessness of its bold architect’s life. Freeing him, indeed, even from the task of explaining his senseless and feverish yearning.